2020
DOI: 10.1158/0008-5472.can-19-3460
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA DRAIC Inhibits Prostate Cancer Progression by Interacting with IKK to Inhibit NF-κB Activation

Abstract: DRAIC is a 1.7 kb spliced long noncoding RNA downregulated in castration-resistant advanced prostate cancer. Decreased DRAIC expression predicts poor patient outcome in prostate and seven other cancers, while increased DRAIC represses growth of xenografted tumors. Here, we show that cancers with decreased DRAIC expression have increased NF-kB target gene expression. DRAIC downregulation increased cell invasion and soft agar colony formation; this was dependent on NF-kB activation. DRAIC interacted with subunit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 63 publications
4
50
0
Order By: Relevance
“…In contrast, several NF-κB-related lncRNAs are down-regulated and function as tumor suppressors during cancer progression. For example, Saha et al [65] reported that the downregulated RNA in cancer (DRAIC) interacted with the subunits of the IκB kinase (IKK) complex and subsequently inhibited prostate cancer progression by repressing IκBα phosphorylation and NF-κB activation. Additionally, the lncRNA keratin 19 pseudogene 3 (KRT19P3) inhibited gastric cancer cell growth and metastasis by modulating IκBα deubiquitination and inactivating NF-κB signalling [66].…”
Section: Nf-κbmentioning
confidence: 99%
“…In contrast, several NF-κB-related lncRNAs are down-regulated and function as tumor suppressors during cancer progression. For example, Saha et al [65] reported that the downregulated RNA in cancer (DRAIC) interacted with the subunits of the IκB kinase (IKK) complex and subsequently inhibited prostate cancer progression by repressing IκBα phosphorylation and NF-κB activation. Additionally, the lncRNA keratin 19 pseudogene 3 (KRT19P3) inhibited gastric cancer cell growth and metastasis by modulating IκBα deubiquitination and inactivating NF-κB signalling [66].…”
Section: Nf-κbmentioning
confidence: 99%
“…We noticed that lncRNA DRAIC had the most significant effect in predicting the prognosis of patients after receiving radiotherapy; lncRNA DRAIC has been shown to inhibit the progression of prostate cancer by interacting with IkB kinase (IKK) and inhibiting NF-kB activity (43). Activation of NF-kB is associated with the radiosensitivity of gliomas (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the differential expression of DRAIC in GC and NC tissues and its potential role in several malignant tumors [10][11][12][13][14][15][16][17], we decided to explore the relationship between DRAIC/ NFRKB and malignant phenotype of GC cells. It was found that DRAIC can restrain the proliferation abilities of HGC-27 and MKN45 cells ( Fig.…”
Section: Biological Effects Of Oedraic and Rescued By Oenfrkb On Gc Cmentioning
confidence: 99%
“…The lncRNA DRAIC gene, which is located on human chromosome 15q23, was reported as a novel tumor regulator in several cancers recently, but it seemed to exhibit different biological effects in cancer cells from different sources [10][11][12][13][14][15][16][17]. On account of the potential value of DRAIC as a GC marker and target, we intended to reveal the expression characteristics and precise mechanism of DRAIC.…”
Section: Biological Effects Of Shdraic On Gc Cellsmentioning
confidence: 99%
See 1 more Smart Citation